Computation Method for the Settlement of a Vertically Loaded Pile in Sloping Ground - Chong Jiang; Wen-yan Wu; Jia-li He; Lu-jie Chen (Advances in Civil Engineering)
Based on the hyperbolic curve tangent modulus method and the wedge stress theory, this paper proposes a calculation method for the settlement of a vertically loaded single pile in sloping ground. By establishing the relationship between the initial tangent modulus and the compression modulus of the slope soil, the tangent modulus of the slope soil is obtained combining with Mindlin-Geddes solution and Hansen formula, and the solution of the pile settlement in sloping ground is derived. Then, a series of numerical analyses are carried out to examine the feasibility of the proposed method. Finally, the effect of parameters is discussed in detail, including the slope angle, the distance of the pile from the slope crest, and the soil properties around the pile. The results show that the pile settlement will increase by increasing the slope angle or decreasing the distance of the pile from the slope crest, and the effect of the two parameters on the pile settlement is coupling-related. Besides, the compression modulus, cohesion, and internal friction angle of the soil around the pile are negatively related to the pile settlement and it is found that the compression modulus of the soil is the more influential parameter.